Evaluation Of Filtering Facepiece Respirators Using Chemical No-Chemical Decontamination Methods - Shobani, Muhamad Hafizuddin Ahmad (Universiti Sains Malaysia, 2021)
COVID-19 has been a catastrophic event for humans as it has infected millions of humans. Due to this, healthcare workers and general public has highly advised the use of Filtering Facepiece Protectors (FFRs) for daily activities. However due to scale of breakout, FFRs are becoming short and insufficient to cope with demand. This experiment aims to evaluate performance of FFRs by characterization of penetration and filter resistance and to determine the effect of decontamination performance to FFRs macrostructure and microstructure. A total of 36 labelled FFRs N95 and KN95 were exposed to four decontamination methods like bleach, vaporized hydrogen peroxide, autoclave, and moisture heat with two N95 and two KN95 FFR as control samples. A filtration performance and airflow resistance test were performed on each of decontaminated FFR. Then, FFR were observed for physical change and significant degradation on its appearance. Next, FFR were taken for microstructure test which was done under Scanning Electron Microscope (SEM) to observe its morphology property. Based on the normalised data of filter penetration and airflow resistance, VHP was the best decontamination method as decontaminated FFR show good performance with least deviation data. As for macrostructure test, Moisture Heat was the only decontamination method which showed no degradation on FFR. As for microstructure test, Bleach decontaminated FFR illustrated the highest fiber breakage and shrinkage occurred on its fiber structure.